Peningkatan Kemampuan Menulis Teks Berita Dengan Metode Kooperatif Jigsaw Pada Siswa Kelas VIII SMP Methodist 9 Medan - Putri Enjel Tarigan; Yemima Rina Yanti Panjaitan; Nur Annisa Fatin; Yandika Lamtorang Gurusinga; Marsela Naomi Sirait; Dara Aisyah; Mustika Wati Siregar (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to improve the ability to write news texts using the Jigsaw type cooperative method in class VIII students at SMP Methodist 9 Medan. The research method used is classroom action research with stages of planning, action implementation, observation, evaluation and reflection. The research results showed that there was an increase in students' ability to write news texts after implementing the Jigsaw cooperative method. This research was carried out from 14 May to 22 May 2024 at SMP Methodist 9 Medan.